2013
DOI: 10.3389/fbioe.2013.00018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Red Blood Cells on Platelet Activation and Thrombus Formation in Tortuous Arterioles

Abstract: Thrombosis is a major contributor to cardiovascular disease, which can lead to myocardial infarction and stroke. Thrombosis may form in tortuous microvessels, which are often seen throughout the human body, but the microscale mechanisms and processes are not well understood. In straight vessels, the presence of red blood cells (RBCs) is known to push platelets toward walls, which may affect platelet aggregation and thrombus formation. However in tortuous vessels, the effects of RBC interactions with platelets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…Aneurysm asymmetry is another factor that is related to increased rupture risk (Fillinger et al 2004; Doyle et al 2009). Buckling deformation changes the blood flow in the aneurysm, which can alter the wall shear stress and affects intra-lumen thrombus distribution (Chesnutt and Han 2011; Chesnutt and Han 2013). While some of these changes are similar to normal arteries (Han 2012), they may be severe in aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Aneurysm asymmetry is another factor that is related to increased rupture risk (Fillinger et al 2004; Doyle et al 2009). Buckling deformation changes the blood flow in the aneurysm, which can alter the wall shear stress and affects intra-lumen thrombus distribution (Chesnutt and Han 2011; Chesnutt and Han 2013). While some of these changes are similar to normal arteries (Han 2012), they may be severe in aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…However, red blood cells are known to push platelets toward vessel walls in straight vessels, and this effect greatly increases the concentration of platelets near walls [60,61]. Hence, we would expect that red blood cells would cause thrombosis to be initiated more quickly than in our simulations.…”
Section: Discussionmentioning
confidence: 74%
“…Hence, we would expect that red blood cells would cause thrombosis to be initiated more quickly than in our simulations. Additionally, after the onset of thrombosis, thrombi and occlusions might form more slowly due to collisions of red blood cells that may detach platelets from thrombi, as seen in our previous work on initial thrombus formation in tortuous microvessels [61]. As well, another computational study of thrombus formation due to an injured section of a plane wall in a simple shear low showed that although the presence of red blood cells resulted in shorter thrombi containing more platelets, the process of thrombus formation in general was not signi icantly affected by the presence of red blood cells [62].…”
Section: Discussionmentioning
confidence: 85%
“…In this section, the computational simulation conditions are described first, followed by descriptions of the employed activation models for platelets and the endothelium. Details of the discrete element method have been previously published [14-16], and a brief description is provided in the Appendix.…”
Section: Methodsmentioning
confidence: 99%
“…Our shear-induced platelet activation model, as developed and applied in [16, 30, 31], assumed that a platelet became activated if it experienced a shear stress above a critical shear stress ( T crit ). This model was in agreement with in vivo and in vitro observations of shear-induced platelet activation and aggregation that occurred within milliseconds [12, 32, 33].…”
Section: Methodsmentioning
confidence: 99%